The safe usage of herbal medicines: counterindications, cross-reactivity and toxicity - Cock, I.E. (Pharmacognosy Communications)
Plants have been used therapeutically for thousands of years and continue to be the main treatment modality for a large percentage of the world’s population. Furthermore, herbal medicine usage is increasing in Western countries as complementary (and sometimes alternative) treatments in conjunction with allopathic medicine. At the same time, the usage of allopathic medicines is being increasingly incorporated into the medicinal systems of developing countries, often resulting in the concurrent usage of both systems. Importance of the Study: Despite the widespread usage in developing countries and the trend of increasing medicinal plant usage in Western countries, herbal medicines remain understudied and there are misunderstandings amongst users and practitioners about the safe usage of these medications, particularly when used in conjunction with other medicines. Herbal medicines are generally not held to the same rigorous standards as allopathic medicines. There is usually a lack of industry regulation and manufacturing standards and guidelines, resulting in inferior (or unsafe) medicines being sold to consumers. Similarly, there is a lack of understanding amongst many medical practitioners of both traditional and allopathic medicine systems of how drugs from the two systems can be safely used together. Aim: The aim of this review is to summarise the current knowledge about herbal medicines and how they can be used safely, with the aim of not only highlighting some of the unsafe uses, but also to stimulate further research. I have also aimed to highlight the need for greater regulation and standardisation of herbal medicines.
Keywords: Drug interactions; pharmacokinetic; pharmacodynamics; drug metabolism; cytochrome P450; side effects; complementary and alternative medicine; quality control